(untitled) (Altre Modernità, 2014)
The essay presents the personal story of Raissa Orlova as an example of a process performed by different writers, primarily women of Jewish origin in the Soviet Union at the beginning of the 20th century. These women no longer have any connection with their ancestors’ religion and try to replace the faith in the Jewish religion with the faith in communism, whose god is Stalin. Raissa Orlova is a perfect example of homo sovieticus: she undertakes the young communist girls’ cursus honorum and she is totally blind to what is happening around her. A fundamental step in her path is the attendance of the IFLI, the "communist school " in Moscow. The veil of illusion falls from her eyes after the Twentieth Party Congress and the comparison with the European reality: Orlova realizes that she has believed in an idol and begins to trace her own personal past, to contrast the unifying vision of communism . At this stage Orlova rediscovers her Jewish origins and, although not converted to her ancestors’ religion, she finally becomes aware of her long ignored past.